Mental health nurse psychotherapists are well situated to improve service shortfalls in Australia: findings from a qualitative study. (August 2020) - Hurley, John; Lakeman, Richard; Cashin, Andrew; Ryan, Tom
Objective: This paper reports the capabilities of mental health nurse (MHN) psychotherapists in Australia and their perceptions on how to best utilize their skills. Method: An MHN is a registered nurse with recognized specialist qualifications in mental health nursing. One hundred and fifty three MHNs completed an online survey; 12 were interviewed. Results: Three themes were derived from a qualitative analysis of the aggregated data: psychotherapy skills of MHN psychotherapists are under-utilized; these nurses bridge gaps between biomedical and psychosocial service provision; and equitable access to rebates in the primary care sector is an obstacle to enabling access to services. Conclusions: MHN psychotherapists are a potentially valuable resource to patients in tertiary and primary health care. They offer capacity to increase access to specialist psychotherapy services for complex and high risk groups, while being additionally capable of meeting patients' physical and social needs. Equitable access to current funding streams including Medicare rebates can enable these outcomes.